FRI0176 Safety of anti-TNF Alfa Agents during Pregancy and Breastfeeding: Longterm Follow up of Exposed Children in A Case-Series of Mothers with Chronic Arthritides. (15th July 2016) - Dall'ara, F.; Reggia, R.; Bazzani, C.; Andreoli, L.; Agosti, M.; Mazza, G.; Lazzaroni, M.G.; Lojacono, A.; Motta, M.; Tincani, A.
Abstract : Background: Anti-TNFalfa agents are used to control disease activity in patients with Chronic Arthritides (Rheumatoid Arthritis, Psoriatic Arthritis, Ankylosing Spondylitis), often during the wash-out period of teratogenic DMARDs and are usually discontinued at positive pregnancy index. However, the presence of a moderate to severe maternal disease activity during pregnancy or puerperium may require the use of the drugs also in the 2nd-3rd trimester and/or in the postpartum period. Few data are available in literature regarding their use in pregnancy and only anecdotal during lactation. Objectives: To compare the health and developmental conditions of children exposed in utero and/or with breastfeeding to anti-TNFalfa agents with non-exposed children born to women with the same disease. Methods: Data on birth, lactation, weaning, growth parameters, developmental milestones, vaccinations and disease conditions were collected submitting an ad-hoc created questionnaire to women affected by chronic arthritides treated with an anti-TNF alfa agent during one or more trimesters of gestation and/or during breastfeeding (cases). Data have been compared to those obtained from mothers affected from the same disease but not exposed to anti-TNF alfa therapy (controls) Results: The table reports the characteristics of 34 cases (15 male, 19 female) (26 exposed to Etanercept, 5 to Adalimumab, 2 to Golimumab and 1 to Certolizumab) and 34 controls (19 M, 15 F). Twenty-six children were exposed during the first trimester (discontinuation of anti-TNFalfa agent at positive pregnancy index), while 8 during the 2nd-3rd trimester (discontinuation at 34th-37th week, mean exposure of 81 days). Both cases and controls underwent vaccinations without any severe complications. Vaccinations were protective; only one child with periconception exposure to etanercept developed chicken-pox despite vaccination. Seven children were breastfed during maternal anti-TNFalfa therapy (5 etanercept, 2 adalimumab): no differences in growth parameters, developmental milestones, vaccinations and diseases in the first year of life were highlighted in comparison to those not exposed to the drugs with lactation. Conclusions: No differences in birth parameters, congenital malformations, and developmental steps in the first 24 months of life have been found between cases and controls. Growth parameters were within the curves of the general population. Cases received more vaccinations than controls. This may be due to the feeling by either parents or paediatricians that these children exposed to immunosuppressive agents could be more susceptible to infectious diseases. No relevant infectious diseases nor post-vaccine complications have been noted in the 6 children exposed to anti- TNFalfa during the 2nd-3rd trimester of gestation nor in the 5 exposed during lactation. Globally, the long-term follow-up of children supports the safety of use of anti-TNFalfa agents, either preconceptionally or during the 2nd-3rd trimester of pregnancy. Data on use during breastfeeding are still anecdotal but can be helpful for counseling the patients who are strongly motivated to breastfeed. Disclosure of Interest: None declared